The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1002/ijc.24568
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of adrenomedullin in renal tumors and value of its mRNA levels as prognostic factor in clear‐cell renal carcinoma

Abstract: Antiangiogenic therapies are used for advanced clear-cell renal carcinomas (cRCC), but without curative possibilities, underlining the need for new therapeutic targets. Adrenomedullin (AM), a multifunctional peptide, is highly expressed in several tumors and plays an important role in angiogenesis and tumor growth through its receptors: calcitonin receptor-like receptor/receptor activity-modifying protein 2 and 3 (CLR/RAMP2 and CLR/ RAMP3). In this study, real-time quantitative reverse-transcription-PCR showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 38 publications
(58 reference statements)
2
49
0
Order By: Relevance
“…RAMP3 mRNA expression is elevated in prostate carcinoma cells as opposed to those from prostate hypertrophy (Mazzocchi et al 2004). In a study of renal tumours, RAMP3 elevation was reported in inflammatory cells associated with the tumour, whereas RAMP2 was found in the tumour cells themselves (Deville et al 2009). This is consistent with a complex role of AM and its receptors, acting directly on the tumour itself and on its environment.…”
Section: Disease Modelssupporting
confidence: 61%
See 2 more Smart Citations
“…RAMP3 mRNA expression is elevated in prostate carcinoma cells as opposed to those from prostate hypertrophy (Mazzocchi et al 2004). In a study of renal tumours, RAMP3 elevation was reported in inflammatory cells associated with the tumour, whereas RAMP2 was found in the tumour cells themselves (Deville et al 2009). This is consistent with a complex role of AM and its receptors, acting directly on the tumour itself and on its environment.…”
Section: Disease Modelssupporting
confidence: 61%
“…This suggests that the antagonist was able to reduce the activity of endogenous AM produced by the tumour or local blood vessels (Ishikawa et al 2003). Moreover, antibodies to the AM 1 and AM 2 receptors inhibited migration and capillary tube formation of endothelial cells and the growth of human tumour xenografts but it is important to note that the specificity of these antibodies has not been properly reported (Fernandez-Sauze et al 2004, Kaafarani et al 2009). …”
Section: Disease Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7,23). Human umbilical venous smooth muscle cells (HUVSMC; ScienCell Research Laboratories, Clinisciences,) were cultured in smooth muscle cell (SMC) growth medium M199 with 20% FBS to confluence.…”
Section: Transwell Migration Assaysmentioning
confidence: 99%
“…To assess programmed cell death, tissue sections were evaluated using mAb F7-26 to detect single-strand DNA (ssDNA; Eurobio AbCys). Staining was carried out as detailed previously (17,23).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%